Evaluation of the dynamic responses of high rise buildings with respect to the direct methods for soil-foundation-structure interaction effects and comparison with the approximate methods - Jahangir Khazaei (Iranian Society of Structrual Engineering (ISSE), 2017)
In dynamic analysis, modeling of soil medium is ignored because of the infinity and complexity of the soil behavior and so the important effects of these terms are neglected, while the behavior of the soil under the structure plays an important role in the response of the structure during an earthquake. In fact, the soil layers and soil foundation structure interaction phenomena can increase the applied seismic forces during earthquakes that has been examined with different methods. In this paper, effects of soil foundation structure interaction on a steel high rise building has been modeled using Abaqus software for nonlinear dynamic analysis with finite element direct method and simulation of infinite boundary condition for soil medium and also approximate Cone model. In the direct method, soil, structure and foundation are modeled altogether. In other hand, for using Cone model as a simple model, dynamic stiffness coefficients have been employed to simulate soil with considering springs and dashpots in all degree of freedom. The results show that considering soil foundation structure interaction cause increase in maximum lateral displacement of structure and the friction coefficient of soil-foundation interface can alter the responses of structure. It was also observed that the results of the approximate methods have good agreement for engineering demands.